2016
DOI: 10.1016/j.brs.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Cervical Vagus Nerve Stimulation Ameliorates Acute Ischemic Injury in Rats

Abstract: Background Direct stimulation of the vagus nerve in the neck via surgically implanted electrodes is protective in animal models of stroke. We sought to determine the safety and efficacy of a non-invasive cervical VNS (nVNS) method using surface electrodes applied to the skin overlying the vagus nerve in the neck in a model of middle cerebral artery occlusion (MCAO). Methods nVNS was initiated variable times after MCAO hour in rats (n=33). Control animals received sham stimulation (n=33). Infarct volume and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 36 publications
(43 reference statements)
6
88
0
Order By: Relevance
“…In addition, a transcutaneous device has been developed that can deliver a proprietary, low-voltage electrical signal to the cervical vagus nerve 64 . In 2016, transcutaneous cervical VNS was reported to protect against cerebral ischaemic injury in rats 65 . In addition, a pilot trial showed that VNS using a gammaCore ® transcutaneous device could downregulate inflammatory cytokine release in healthy individuals 66 .…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%
“…In addition, a transcutaneous device has been developed that can deliver a proprietary, low-voltage electrical signal to the cervical vagus nerve 64 . In 2016, transcutaneous cervical VNS was reported to protect against cerebral ischaemic injury in rats 65 . In addition, a pilot trial showed that VNS using a gammaCore ® transcutaneous device could downregulate inflammatory cytokine release in healthy individuals 66 .…”
Section: Vagus Nerve Stimulationmentioning
confidence: 99%
“…In recent years the major sites of interest for delivering electrical stimulation to the ABVN have been the inner surface of the tragus (Busch et al, 2013;Clancy et al, 2014;Kraus et al, 2013;Stavrakis et al, 2015;Weise et al, 2015;Zhou et al, 2016), the concha (Ay et al, 2015b;Fang et al, 2015;He et al, 2013b;Liu et al, 2013), and the cymba concha (Frangos et al, 2015;Kreuzer et al, 2014). In parallel with these ear studies, a method said to allow non-invasive cervical vagus nerve stimulation through the skin of the neck has also been developed and is under investigation in patients with cluster headache (Nesbitt et al, 2015) and migraine (Barbanti et al, 2015).…”
Section: Cardiac Effects Of Tvnsmentioning
confidence: 99%
“…Likewise, the electroCore LLC gammaCore device (Basking Ridge, NJ, USA) is a non‐invasive VNS to treat primary headache. Meanwhile, tVNS has been tested in several pilot trials including treatment of migraine depression and epilepsia in humans and in rodent models of epilepsia, stroke and pain relief. However, the effect of tVNS has not been tested in models of peripheral inflammatory diseases for example POI.…”
Section: Introductionmentioning
confidence: 99%